ANALISIS KEMAMPUAN DAYA SERAP RUANG TERBUKA HIJAU TERHADAP EMISI KENDARAAN BERMOTOR DI KECAMATAN SIDOARJO DAN BUDURAN (STUDI KASUS MASA PANDEMI COVID – 19 - Naniek Ratni JAR; Nurfadilla Rizki Aprilia (EnviroUS, 2022)
Permendagri Number 1 of 2007 concerning RTHKP arrangement which is a detailed elaboration of Law Number 26 of 2007 concerning Spatial Planning stipulates that the ideal area of RTHKP is at least 30% of the urban area. This study aims to evaluate the percentage of Green Open Space (RTH) required in the area to be able to absorb emissions generated by transportation activities. The method used is the determination of the estimated carbon dioxide emissions (CO2). Based on the results of the study, it was found that the absorption capacity of green open space on carbon dioxide (CO2) emissions in Abhirama Park was 20,888,389.92 g/day and 9,118,932.24 g/day in Sidoarjo Square.